FEMINISM AT THE CROSSROADS OF FAITH AND SOCIAL POWER IN DOROTHEA ROSA HERLIANY’S PEREMPUAN BERDOSA - Yoga Sudarisman; Rachmat Nugraha; Ana Lustiyowati; Dindin Solahudin; Yusuf Zainal Abidin (Fakultas Adab dan Humaniora UIN Sunan Gunung Djati Bandung, 2025)
This article examines the female body within a feminist framework that operates at the intersection of religion and social space through a reading of Dorothea Rosa Herliany’s poem Perempuan Berdosa. The poem portrays a woman burdened by accusations of sin and by the symbolic violence imposed upon her body by society. Images of being hunted, pressed down, and judged reveal how religious and social norms often position women as the source of moral wrongdoing. Feminist analysis challenges these patterns by asserting that women possess voices and lived experiences that cannot be reduced to moral stigma. Through this poetic reading, the article argues that the female body can become a site of resistance against patriarchal control and unjust moral scrutiny. Women’s awareness of their bodies and experiences opens possibilities for renegotiating identity, spirituality, and their place within everyday social life.